The given equation can be written as
"(6D^{2}-5DD'-6D'^{2})u=52e^{3x+2y}", where "D \\equiv \\dfrac{\\partial}{\\partial x}, D' \\equiv \\dfrac{\\partial}{\\partial y} ."
The auxiliary equation is
"6m^{2}-5m-6=0" , solving we get
"m = -\\dfrac{2}{3}, \\dfrac{3}{2}"
"C.F=f_{1}(y-\\frac{2x}{3})+f_{2}(y+\\frac{3x}{2})"
"P.I = \\dfrac{1}{6D^2-5DD'-6D'^{2}} 52e^{3x+2y}\\\\\n~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~\\text{(Replace $D$ by 3 and $D'$ by 2)}\\\\\n= \\dfrac{1}{6 \\cdot 3^2-5\\cdot 3\\cdot 2-6\\cdot2^{2}} 52e^{3x+2y}\\\\\n= \\dfrac{1}{0}52e^{3x+2y}~~\\text{(Rule fails)}\\\\\n~~~~~~~~~~~~~~~~~~~~~~~~~~\\text{(Differentiating denominator with respect to $D$} \\\\\n~~~~~~~~~~~~~~~~~~~~~~~~~~~~\\text{and multiplying the numerator by $x$)}\\\\\n=x \\dfrac{1}{12 D-5D'} 52e^{3x+2y}\\\\\n~~~~~~~~~~~~~~~~~~~~~~~~~~\\text{(Replace $D$ by 3 and $D'$ by 2)}\\\\\n=x\\dfrac{1}{36-10}52e^{3x+2y}\\\\\nP.I=2xe^{3x+2y}"
The general solution is
"u(x,y) = C.F+P.I = f_{1}(y-\\frac{2x}{3})+f_{2}(y+\\frac{3x}{2})+2xe^{3x+2y}"
Comments
Leave a comment